Rationes decoris Aufkommen und Verbreitung dorischer Friese in der mittelitalischen Architektur des 2. und 1. Jahrhunderts v. Chr. - Maschek, Dominik (Phoibos Verlag, 2012)
The core of the book consists in the coherent typological analysis of more than 200 Doric friezes from hellenistic Central Italy. By means of this data a typologically induced dating and historical evaluation for each building became possible. Several stages of motivic and stylistic transfer concerning sacred and funeral buildings can be linked to different processes of political restructuring, spanning the period from the Social War to the veteran settlements and municipalisation of Early Augustan times.